Peran Literasi Pajak dalam Menurunkan Tingkat Tunggakan PBB oleh Pelaku UMKM: Pengabdian - Halawa, Erimina; Lamsah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This Community Service Program (PKM) aims to improve tax literacy and financial record-keeping skills among Micro, Small, and Medium Enterprises (MSMEs) in the production sector, who continue to face limited understanding of tax obligations, particularly the Land and Building Tax (PBB). Low tax literacy causes MSME actors to be unable to calculate the amount of PBB payable, understand payment deadlines, follow payment procedures, and recognize the legal consequences of late payments, which in turn contributes to high levels of tax arrears. To address these issues, the PKM activities were designed through three stages: preparation, a one-day training session, and three weeks of mentoring. The training was conducted through lectures, simulations, and hands-on practice in recording financial transactions, preparing a daily cash book, developing a simple income statement, and performing simulations of PBB calculation and payment. The mentoring phase was carried out online to ensure participants consistently applied the financial recording techniques that had been taught. The results of the program show a significant improvement in participants’ understanding of financial recording, tax awareness, and their ability to calculate and pay PBB independently. This program proved effective in fostering more disciplined administrative practices and has the potential to reduce PBB arrears among MSMEs in the production sector.